2005
DOI: 10.1192/apt.11.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention in psychosis: obstacles and opportunities

Abstract: By focusing therapeutic effort on the early stages of psychotic disorders, effective early intervention should improve short- and long-term outcomes. Strategies include pre-psychotic and prodromal interventions to prevent emergence of psychosis, detecting untreated cases in the community and facilitating recovery in established cases of psychosis. The evidence base for each of these strategies is currently limited, although several international trials are under way. The Department of Health in the UK has anno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…We examined two subgroups according to age criteria: those traditionally eligible for entry to Early Intervention Services in the UK (16 to 35 years old)[26], [27] those eligible for entry to General Adult psychiatric services (16 to 65 years old).…”
Section: Methodsmentioning
confidence: 99%
“…We examined two subgroups according to age criteria: those traditionally eligible for entry to Early Intervention Services in the UK (16 to 35 years old)[26], [27] those eligible for entry to General Adult psychiatric services (16 to 65 years old).…”
Section: Methodsmentioning
confidence: 99%
“…The team is multi-disciplinary in approach and provides a comprehensive package of community-based care for a maximum of 2 years to young people with a first episode of psychosis. For more details see Singh and Fisher (2005).…”
Section: Clinical Teammentioning
confidence: 98%
“…A stand‐alone specialist team with trained staff and small caseloads is advocated as the gold standard to deliver the model, but is not always feasible to implement. Alternative approaches embed EPI delivery within general mental health teams, supported by strategies such as whole team education, training of selected team staff as EPI specialists, providing protocols for identifying and managing first‐episode clients, supervision by EPI specialists, protecting staff time for EPI delivery and establishing area early intervention networks . Studies have shown that alternative models can deliver the complement of services that constitute EPI, with positive results …”
Section: Introductionmentioning
confidence: 99%